Saxagliptin: A potential doping agent? A randomized, double‐blinded, placebo‐controlled, and crossover pilot study in young active men. Issue 23 (2nd December 2022) - Bourdillon, Nicolas; Eugster, Philippe J.; Vocat, Céline; Nguyen, Toan; Wuerzner, Gregoire; Grouzmann, Eric; Millet, Grégoire P.
Abstract: Neuropeptide Ys (NPYs) contribute to sympathetic‐adreno stimulation: NPY1‐36 potentiates the effects of catecholamines (CATs), whereas NPY3‐36 inhibits CAT release. We sought to investigate whether inhibiting dipeptidyl‐peptidase‐4 (DPP4), cleaving NPY1‐36 into NPY3‐36, leads to increased NPY1‐36 potentiating effects and reduced NPY3‐36 inhibitory effects on CATs, thereby improving endurance performance. Seven male participants (age 27 ± 3 years, BMI 23.1 ± 2.4 kg/m 2 ) performed time‐to‐exhaustion cycling exercise at 95% of peak power output with either placebo, or saxagliptin, a DPP4 inhibitor. Oxygen consumption (V̇O2 ), heart rate variability, NPY1‐36, NPY3‐36, catecholamines, and lactate were measured at several time points before, during, and after exercise. With saxagliptin, DPP4 activity (12.7 ± 1.6 vs. 0.2 ± 0.3 U/L, p = 0.001; d = 10.7) was decreased at rest, while NPY3‐36 (1.94 ± 0.88 vs. 0.73 ± 0.22 pm ; p < 0.001; d = 2.04) decreased and NPY1‐36 increased during exercise (2.64 ± 2.22 vs. 4.59 ± 2.98 pm ; p < 0.01; d = 0.19). CATs were unchanged. Time‐to‐exhaustion was 32% higher with saxagliptin. The difference in time‐to‐exhaustion between placebo and saxagliptin was correlated with NPY1‐36 differences (R = 0.78, p < 0.05). Peak V̇O2 and other cardio‐respiratory values were not different, whereas peak NPY concentrations were higher with saxagliptin. DPP4 blockade improved performance, increased NPY1‐36, and decreased NPY3‐36 concentrations which may have potentiating effects on the influences of CATs. However, DPP4 is involved in many different actions, thus NPYs are one group of factors that may underly its performance‐enhancing effects; further studies are required to determine the exact mechanisms.